Implants for surgery - Hydroxyapatite - part 1: Ceramic Hydroxyapatite (ISO 13779-1:2008, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Mohd Yusof, Hyzan; et al. (SIRIM Berhad, 2010)
ISO 13779-1:2008 specifies requirements for ceramic hydroxyapatite intended for use as surgical implants.